Patterns of paediatric emergency presentations to a tertiary referral centre in the Northern Territory. (8th November 2017) - Buntsma, Davina; Lithgow, Anna; O'Neill, Evan; Palmer, Didier; Morris, Peter; Acworth, Jason; Babl, Franz E
Abstract: Objective: To describe epidemiological data concerning paediatric attendances at the ED of Royal Darwin Hospital (RDH). Methods: We conducted a retrospective cohort study of paediatric emergency presentations to the RDH ED during 2004 and 2013. Epidemiological data, including demographics, admission rates and diagnostic grouping, were analysed using descriptive and comparative statistical methods. We compared data with findings from a baseline epidemiological study by the Paediatric Research in Emergency Departments International Collaborative (PREDICT) conducted in 2004. Results: A total of 12 745 and 15 378 paediatric presentations (age 0–18 years) to the RDH ED were analysed for the years 2004 and 2013 respectively. In 2004, the mean age of children presenting to RDH was 7.1 years, and 56.0% were female. Indigenous patients accounted for 31.2% of presentations at RDH and were significantly more likely to be admitted than non‐Indigenous patients (31.6% vs 12.8%, OR 3.24, 95% CI 2.95–3.55). Children <5 years old accounted for the highest number of presentations (45.2%) and admissions (51.2%), and there was a high proportion of adolescent presentations (18.0%). Similar to the PREDICT study, viral infectious conditions (bronchiolitis, gastroenteritis, upper respiratory tract infections) were the most common cause for presentations. Key differences included a higher proportion of patients presenting with cellulitis and head injury at RDH and an increasing proportion of adolescent psychiatric presentations at RDH from 2004 to 2013. Conclusion: This study provides important information regarding paediatric presentations to a major referral hospital in the Northern Territory. Overall, there was a disproportionate rate of presentation and admission among Indigenous children. Other key findings were higher proportions of cellulitis, head injury and adolescent presentations. These findings can assist in service planning and in directing future research specific to children in the Northern Territory.